2007
DOI: 10.2135/cropsci2006.10.0687
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Peroxidase Activity in Maize Endosperm Associated with Maize Weevil Resistance

Abstract: Plant peroxidases (PODs) are involved in resistance to pathogens and insects. This study investigated the role of POD in maize (Zea mays L.) resistance to the maize weevil, Sitophilus zeamais (Motsch.). Insect bioassays were performed under controlled conditions to assess maize weevil resistance. Peroxidase activity was measured in the major grain tissues using guaiacol and peroxide. Significant variation (P > 0.001) among genotypes was observed in both the insect bioassay traits and POD activity. Peroxidase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 17 publications
0
49
0
3
Order By: Relevance
“…Enhanced cell wall lignification can fortify physical barriers and increase indigestibility to attacking pests. Indeed, class III peroxidases have been linked to host resistance to a wide range of insects (Dowd and Lagrimini, 2006;Garcia-Lara et al, 2007) and pathogens (Choi et al, 2007;Johrde and Schweizer, 2008). It is possible that different mechanisms are deployed against different pests through activation of different class III peroxidases.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced cell wall lignification can fortify physical barriers and increase indigestibility to attacking pests. Indeed, class III peroxidases have been linked to host resistance to a wide range of insects (Dowd and Lagrimini, 2006;Garcia-Lara et al, 2007) and pathogens (Choi et al, 2007;Johrde and Schweizer, 2008). It is possible that different mechanisms are deployed against different pests through activation of different class III peroxidases.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to maize weevils is related to certain physical factors such as kernel hardness (Dobie 1977) nutritional factors such as carbohydrates, lipids and proteins, or non-nutritional factors, such as phenolic compounds (Arnarson et al 1992). García-Lara et al (2007) also reported that some of the mechanisms for weevil resistance are associated with protein, fibre, and various pericarp cell phenolic acid compounds, structural proteins and enzymes such as peroxidase.…”
Section: Introductionmentioning
confidence: 99%
“…Information on gene action well help determine maize weevil resistance in designing strategies to develop resistant maize varieties (Derera et al 2000;Dhliwayo et al 2005). A greater understanding of the biochemical and structural mechanisms of weevil resistance in maize grain suggests opportunities for molecularassisted breeding strategies (García-Lara et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Maize hybrids that exhibit low grain weight loss for example, CZH131022 are often characterized with high levels of phenolic compounds. Different phenolic compounds such as coumaric acid esterified to carbohydrates on the maize pericarp tend to discourage successful utilization of a maize variety as an ideal host by an insect thereby resulting in low percentages of grain weight loss (García-Lara et al, 2007). As suggested by the results (Table 3), there is high variation in kernel volume amongst all drought tolerant maize hybrids evaluated for weevil resistance in this particular study.…”
Section: F1 Weevil Progeny Emergence (F 1 Wpe) Percentage Grain Weigmentioning
confidence: 72%